Report to the county of Lanark, of a plan for relieving public distress, and removing discontent, by giving permanent, productive employment, to the poor and working classes, under arrangements which will essentially improve their character, and ameliorate their condition, diminish the expenses of production and consumption, and create markets co-extensive with production - Owen, Robert (1771-1858)
ill. En appendice : "Prospectus of a plan for establishing an institution on Mr. Owen's system in the middle ward of the County of Lanark"